Experiences of sexual and reproductive health screening and counseling in the clinical setting among adolescents and young adults with rheumatic disease - Brittany Huynh; Mary A. Ott; Stacey E. Tarvin (Pediatric Rheumatology Online Journal)
Abstract Background Our objective was to describe differences among adolescents and young adults (AYAs) with rheumatic disease using teratogens compared to non-users in receipt of sexual and reproductive health (SRH) counseling, teratogenicity knowledge, perceived importance of SRH topics, and preferences around counseling. Methods AYAs ages 14–23 years and assigned female at birth were recruited from pediatric rheumatology clinics at a Midwest tertiary care program. Participants completed a one-time online survey assessing SRH. Results One-hundred eight participants completed the survey, representing a range of rheumatic diseases. 24% reported ever having sex. 36% used a teratogen. Rates of screening and counseling regarding SRH topics were low. Notably, pregnancy prevention and emergency contraception (EC) counseling by rheumatologists were uncommon and not associated with teratogen use or sexual activity. Among AYAs on teratogens, only half reported screening for sexual activity or counseling on teratogenicity or pregnancy prevention. Gaps in pregnancy prevention and EC counseling remained even when accounting for counseling by other providers. Knowledge of medication teratogenicity was also low. AYAs reported SRH topics of high importance, and many reported recent concerns. They preferred to receive information from their rheumatologist, and most agreed it is important to talk to their rheumatologist regarding these topics. Conclusions AYAs with rheumatic disease report low levels of SRH screening and counseling by their rheumatologist yet report these topics are important and want to discuss them. Gaps in teratogenicity knowledge were identified. This study identifies a need for improved communication with AYAs regarding their SRH.